Working with young people - Curran, Sheila (Senior lecturer); Harrison, Roger, 1953-; MacKinnon, Donald, 1947-; Open University (Los Angeles, California : Sage, 2013)
Working with Young People is designed to help you develop the knowledge and skills you need for supporting young people as they learn about themselves, others and society and prepare for the transition to adulthood. It introduces the fundamental concepts and issues that lie at the heart of contemporary work with young people and challenges you to think deeply about: - the social context of young people - values and principles that underpin practice - the variety of settings in which practice takes place, and - the importance of informal learning in the lives of young people. Whether you are a new student or returning to study, Working with Young Poeple provides a stimulating introduction and a foundation for further study.
Young people in society. Policy, practice and research in work with young people -- Youth as a social construction -- Trouble and tribes : young people and community -- Teenage pregnancy and parenthood : implications for policy and practice -- What does the 'teen brain' research say, and what does it mean for practitioners? -- Youth work in a cold climate -- The nature of work with young people. Defining good youth work -- Every day is different -- Helping : definitions and purpose -- Informal learning in youth work : times, people and places -- Thinking ethically -- A social theory of learning -- The practices of work with young people. Crossing boundaries? Working informally in formal settings -- Enhancing young people's participation -- Developing generative themes for community action -- Working with groups of young people -- Youth work in a digital age. Faith-based youth work -- lessons from the christian sector -- Supervision as a youth work tool.
Previous edition: 2005.
Published in association with the Open University.
Includes bibliographical references and index.
Keywords: Social work with youth -- Great Britain; Social work with youth; Great Britain